Application of Fault Tolerant Controller Based on RBF Neural Networks for Mobile Robot - Zheng Li (2009 International Symposium on Intelligent Ubiquitous Computing and Education : 15-16 May 2009, 2009)
This paper presents a method based on RBF neural networks for achieving fault tolerant control in the mobile robot control scheme. Tuning rules of the RBF networks which guarantees the stability of the fault system were derived and the on-line fault tolerant control scheme was developed. The method does not need fault detection and diagnosis modules. As an example of the application, a tracking control problem for the speed and azimuth of a mobile robot driven by two independent wheels is solved by using the controller. The effectiveness of the proposed method is illustrated by performing the simulation of a circular trajectory tracking control.